(untitled) (KYAMC Journal, 2023)
Background: Sleeping is the body’s natural means of recharging, which aids in repair, healing, and learning from all interactions and activities during the day. To maintain their focus, concentration, and academic performance, students need to get enough sleep at night. Objective: To determine and compare the sleep quality of 278 undergraduate medical and university students. Materials and Methods: This online-based cross-sectional study was conducted by using a pre-tested semi-structured questionnaire with Pittsburgh Sleep Quality Index (PSQI) scale. Results: The mean age of medical students were 22.6±1.5 years and university students were 22.0±1.2 years. The mean study hours in a day, spending time on digital media and BMI were almost similar in both settings students. The mean PSQI scores were 7.2±3.3 in medical students and 6.4±3.3 in university students respectively. Majorities of the students (71.2% and 58.3%) had poor sleep quality, but subjective sleep quality was good in both settings of students (60.4% and 51.8%). Educational backgrounds were significantly associated with level of sleep quality, level of subjective sleep quality and mean of PSQI scores (p<0.05). Conclusion: This study demonstrates that sleep quality is poor among public medical college students compared to university students. KYAMC Journal Vol. 13, No. 04, January 2023: 223-228